Interval laparoscopic appendectomy after antibiotic therapy for appendiceal abscess in elderly patients. Issue 3 (16th October 2019) - Mima, Kosuke; Miyanari, Nobutomo; Itoyama, Rumi; Nakao, Yosuke; Kato, Rikako; Shigaki, Hironobu; Kurashige, Junji; Inoue, Mitsuhiro; Iwagami, Shiro; Mizumoto, Takao; Kubota, Tatsuo; Baba, Hideo
Abstract: Introduction: The aim of this study was to evaluate the safety and efficacy of interval laparoscopic appendectomy after antibiotic therapy in elderly patients with appendiceal abscess. Methods: We retrospectively analyzed data for 50 patients with appendiceal abscess aged ≥18 years who had initially planned to undergo interval laparoscopic appendectomy after antibiotic therapy and 50 patients with appendicitis aged ≥70 years who had undergone early laparoscopic appendectomy. All patients were treated at the National Hospital Organization Kumamoto Medical Center between 2012 and 2018. We compared perioperative outcomes after interval appendectomy between patients aged <70 years and ≥70 years. Results: Clinical progression of appendicitis during antibiotic therapy developed in one patient (2.0%), and recurrent appendicitis after antibiotic therapy for appendiceal abscess occurred in two patients (4.0%). Pathological findings confirmed appendiceal neoplasms in four patients (8.0%). Postoperative infectious complications occurred in 1 of 47 patients (2.1%) who had undergone successful interval laparoscopic appendectomy, and the median length of postoperative hospital stay was 4 days (interquartile range, 3‐5 days). There were no significant differences in outcomes after interval appendectomy between patients aged <70 years and ≥70 years. In the secondary analysis, the median length of postoperative hospital stay after interval laparoscopic appendectomy for appendiceal abscess (4 days) was significantly shorter than that after early laparoscopic appendectomy for uncomplicated appendicitis (7 days; P  < .001). Conclusions: Interval laparoscopic appendectomy for appendiceal abscess may be safe and effective in elderly patients without severe comorbidities. Interval appendectomy may be necessary for determining the underlying cause of appendiceal abscess in adults.